1997
DOI: 10.1007/bf01300565
|View full text |Cite
|
Sign up to set email alerts
|

Berufsbedingte degenerative Diskopathien im Lendenwirbels�ulenbereich

Abstract: A case-control study comprising 188 male and 160 female cases from an orthopedic's cabin explained occupational risk factors for osteochondrosis, spondylosis, and spondylarthrosis of the lumbar vertebra. The controls (109 men, 130 women) steaming mainly from other physician's offices were free from musculoskeletal symptoms. Age-adjusted odds ratio (OR) were calculated for both sexes. In women elevated ORs were found for working in standing position (OR 2.2 CI 1.31-3.85), for repetitive work (OR 1.9 CI 1.17-3.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…To the authors' knowledge, there is only one previous study that has focussed separately on this outcome, and that was a German case-control study on men and women (N ¼ 587) attending an orthopaedic outpatient clinic. In that study, working in a cold environment was associated with degenerative lumbar disc disease in men (OR 2.20;, but not in women (OR 1.60; 95% CI 0.78-3.31) (Elsner, Nienhaus, and Beck 1997).…”
Section: Main Findings and Interpretationmentioning
confidence: 78%
See 1 more Smart Citation
“…To the authors' knowledge, there is only one previous study that has focussed separately on this outcome, and that was a German case-control study on men and women (N ¼ 587) attending an orthopaedic outpatient clinic. In that study, working in a cold environment was associated with degenerative lumbar disc disease in men (OR 2.20;, but not in women (OR 1.60; 95% CI 0.78-3.31) (Elsner, Nienhaus, and Beck 1997).…”
Section: Main Findings and Interpretationmentioning
confidence: 78%
“…Looking at distinct sites of pain in the locomotor system, a narrative review from 2002 on ten scientific articles reported on several studies that indicated an association between cold work and low back pain (Pienim€ aki 2002). Data on neck pain was scarce, and only one study had investigated effects on lumbar disc diseases (Elsner, Nienhaus, and Beck 1997). Another review from the same year, based on 27 scientific articles, described the epidemiological evidence for cold-related MSD as very weak, and called for further studies (Hildebrandt et al 2002).…”
Section: Previous Knowledge On Cold Exposure Effectsmentioning
confidence: 99%
“…125 Exclusion for graph only * 27 No outcome of interest [6, 10, 1230, 3135], 11 no non-exposed group [3646], 23 not evaluating occupational load [1, 4753, 5462], 19 not a cohort study [63–81], 11 included patients on already established conditions, [37, 8291] 5 no imaging on all groups [92–96], 4 cervical spine [97–100], 1 in vitro, [101] 1 child study [34], 1 cant get full text [102], 3 secondary analysis or study with same population of an already included study, [103105] 10 studies evaluated whole body vibration alone, [106–115] 9 studies evaluated athletes [116124].…”
Section: Resultsmentioning
confidence: 99%